Is the Otolithic Function Affected in Patients with Obstructive Sleep Apnea Syndrome? - Ozses, Merve; Mungan Durankaya, Serpil; Guneri, Enis A.; Öztura, İbrahim; Ecevit, Mustafa C.; Ellidokuz, Hülya; Kirkim, Günay (Journal of the American Academy of Audiology, 2024)
Background While cardiovascular and neurological diseases induced by obstructive sleep apnea syndrome (OSAS) hypoxia are well established, the association between neuro-otological diseases and OSAS is not entirely understood. Vestibular and audiological tests have been used to evaluate the degeneration of neurons in the brainstem caused by recurrent hypoxia.Purpose Evaluation of the vestibular-evoked myogenic potential (VEMP) test findings applied to detect the possible influence on the vestibular reflex arc due to hypoxia in patients diagnosed with OSAS using Activity-Specific Balance Confidence (ABC) and Berg Balance Scale (BBS) scales determination of scores.Research Design This was a cross-sectional study.Study Sample Participants aged 18 to 60 who underwent polysomnography due to snoring/sleep apnea were divided into an OSAS, and a control group of subjects were also included. Each group consisted of 20 participants.Data Collection and Analysis All participants were evaluated with cervical VEMP (cVEMP) and ocular VEMP (oVEMP) tests. The groups were compared regarding variables such as the rate of oVEMP and cVEMP waves obtained, the interval between the waves, and the latency and amplitude. Also, BBS and ABC scales were applied to all participants.Results The cVEMP (50%) and oVEMP (45%) response rates and amplitudes were significantly lower in the OSAS group. No significant difference was found between the groups when comparing other VEMP parameters. However, a statistically significant decrease was observed in the ABC and BBS scores in the OSAS group.Conclusion The identification of VEMP alterations in the OSAS group is a clear indication that the vestibular reflex pathways may be adversely affected by hypoxia. Personal rehabilitation programs can be created by evaluating activities of daily living with the ABC and static and dynamic balances with BBS in patients with OSAS.
Keywords: cervical; ocular; VEMP; obstructive sleep apnea